Rational or emotional user: the dual processing approach to understanding continuance usage - Bravo, Edgardo (2023)
Understanding why users continue or discontinue using specific technology is vital for its providers. Existing literature has explored the reasons for continuance and discontinuance by taking into account both rational and emotional factors. However, one question remains unanswered: Why do some users depend more on rational factors for decision-making, while others rely more on emotional factors? This study addresses this question by integrating cognitive decision-making styles and the fear of making incorrect decisions into traditional continued usage models. Data were gathered from 285 TV users and analyzed using structural equation modeling. The results demonstrate that the introduced constructs moderated the direct effects of rational and emotional factors. The contribution of the study lies in incorporating the underlying cognitive processes of decision-making. It presents two actionable variables that managers can utilize to categorize their customers and enhance the effectiveness of their use continuance strategies.